Optimized protocol to preserve RNA integrity for laser capture microdissection of bovine mammary epithelial cells - Ratan Kumar Choudhary; Thomas B. McFadden; Erin M. Shangraw; Feng-Qi Zhao (JDS Communications, 2025)
Laser capture microdissection (LCM) is a popular technique for isolating specific cell types from tissues for medical research. However, the LCM procedure for isolating bovine mammary epithelial cells (MEC) for high-throughput transcriptome profiling has been lacking. The quality and quantity of RNA in LCM samples can be significantly affected by tissue treatment, time for dissection, and the total area of cells dissected. The objective of this study was to optimize the procedures for isolating bovine MEC from mammary tissues for consistent isolation of intact RNA suitable for downstream high-throughput RNA sequencing. Mammary tissues were biopsied (approximately 10–15 min per biopsy) from lactating cows, stored at −80°C, cryosectioned, and processed for LCM. Using LCM software, closed lines were selected and drawn around MEC visible within the alveoli of stained sections and microdissected. Degradation of MEC RNA was minimized by minimal exposure of tissue to aqueous media, the addition of RNase inhibitors in staining solution, and reducing LCM dissection time to less than 15 min (13.6 ± 0.52 min; mean ± SEM). Results showed that tissue fixation with chilled 70% ethanol, histone staining (with RNase inhibitor), dehydration in absolute ethanol, and final clearing in xylene preserved the RNA quality compared with staining sections without RNase inhibitor, no xylene clearing, and longer microdissection times. Using this approach, high-quality RNA was successfully obtained for RNA sequencing.